Detection of downhole incidents for complex geological drilling processes using amplitude change detection and dynamic time warping. (June 2021) - Li, Yupeng; Cao, Weihua; Hu, Wenkai; Wu, Min
Abstract: Geological drilling process is operating under complex geological conditions, which may lead to a high risk of downhole incidents and thus compromise the drilling efficiency. To achieve prompt detection of downhole incidents and prevent them from developing to serious drilling accidents, this paper proposes a new data-driven detection method for downhole incidents based on the amplitude change detection and dynamic time warping. Two major phases are involved: the change monitoring phase detects whether there is any significant change in the drilling signals and extracts variational trend features by linear fitting and amplitude change detection; the incident detection phase determines if the cause of a change is a normal switching or a downhole incident by similarity analysis based on the dynamic time warping and the density-based spatial clustering. Industrial case studies show that the proposed method achieves good performance in downhole incidents detection for geological drilling processes. Highlights: This work proposes a new data-driven method to detect downhole incidents. A change monitoring approach is presented to detect signal amplitude changes. A similarity analysis technique is developed based on DTW and DBSCAN.